2015
DOI: 10.1038/aps.2014.136
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide reduces the body weight and waist circumference in Chinese overweight and obese type 2 diabetic patients

Abstract: Aim: To investigate the effects of liraglutide, a glucagon-like peptide-1 (GLP-1) receptor activator, on body weight and waist circumference in Chinese overweight and obese type 2 diabetic patients. Methods: A total of 328 Chinese overweight and obese type 2 diabetic patients were included in this multi-center, open-labeled and self-controlled clinical study. The patients were subcutaneously injected with liraglutide once daily for 24 weeks as add-on therapy to their previous hypoglycemic treatments. Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
4
19
1
Order By: Relevance
“…Both baseline BMI and female gender were the main determinants of the decrease in body weight, which occurred independently from other clinical or biochemical features or Liraglutide dosage (1.2 or 1.8 mg). These findings are partially in line with those reported in a Chinese population [24], in which patients with higher baseline BMI values showed greater body weight reduction after 24 weeks of Liraglutide treatment, and in a Northern East Italian cohort [25], where weight loss was related with baseline body weight. Also, the results of this study are in agreement with earlier investigations by our group, which showed the impact of female gender on the glycemic effectiveness of Liraglutide [26].…”
Section: Discussionsupporting
confidence: 90%
“…Both baseline BMI and female gender were the main determinants of the decrease in body weight, which occurred independently from other clinical or biochemical features or Liraglutide dosage (1.2 or 1.8 mg). These findings are partially in line with those reported in a Chinese population [24], in which patients with higher baseline BMI values showed greater body weight reduction after 24 weeks of Liraglutide treatment, and in a Northern East Italian cohort [25], where weight loss was related with baseline body weight. Also, the results of this study are in agreement with earlier investigations by our group, which showed the impact of female gender on the glycemic effectiveness of Liraglutide [26].…”
Section: Discussionsupporting
confidence: 90%
“…The effect of GLP-1 administration on HOMA has been previously studied [14,15]. In our study, all the three kinds of treatment showed statistically significantly lower insulin resistance and higher insulin secretion compared with baseline.…”
Section: Discussionsupporting
confidence: 52%
“…As increased BMI impairs GLP-1 secretion and aggravates insulin resistance, the supraphysiological infusions of GLP-1 may act as a positive feedback signal in obese patients to improve insulin sensitivity and reduce chronic obesity. Although the underlying mechanism is only partly understood, several previous studies on liraglutide intervention reported that patients with higher BMI achieved greater body weight loss, suggesting that GLP-1RAs guarantee stable weight maintenance on lean patients 41 , 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%